2014
DOI: 10.5658/wood.2014.42.5.605
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure of Cured Urea-Formaldehyde Resins Modified by Rubber Latex Emulsion after Hydrolytic Degradation

Abstract: This study investigated microstructural changes of cured urea-formaldehyde (UF) resins mixed with aqueous rubber latex emulsion after intentional acid etching. Transmission electron microscopy (TEM) was used in order to better understand a hydrolytic degradation process of cured UF resins responsible for the formaldehyde emission from wood-based composite panels. A liquid UF resin with a formaldehyde to urea (F/U) molar ratio 1.0 was mixed with a rubber latex emulsion at three different mixing mass ratios (UF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Some studies focused on the mechanism by which the hydrolysis of UF resins was achieved via the loss of bond strength and the release of formaldehyde (FE) in neat cured UF resin [10,11,12,13,14,15,16] and UF resin-bonded wood panels [17,18,19,20]. Recently, the hydrolysis of cured UF resins using acid was undertaken to determine the micro-morphology of the sample with the aid of scanning electron microscopy (SEM) [21], transmission electron microscopy (TEM) [22], and Confocal laser scanning microscopy (CLSM) [23]. The results of this investigation indicated that the cured UF resins were composed of amorphous regions which were removed under acid etching and crystalline parts that underwent decomposition after extended reaction periods.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies focused on the mechanism by which the hydrolysis of UF resins was achieved via the loss of bond strength and the release of formaldehyde (FE) in neat cured UF resin [10,11,12,13,14,15,16] and UF resin-bonded wood panels [17,18,19,20]. Recently, the hydrolysis of cured UF resins using acid was undertaken to determine the micro-morphology of the sample with the aid of scanning electron microscopy (SEM) [21], transmission electron microscopy (TEM) [22], and Confocal laser scanning microscopy (CLSM) [23]. The results of this investigation indicated that the cured UF resins were composed of amorphous regions which were removed under acid etching and crystalline parts that underwent decomposition after extended reaction periods.…”
Section: Introductionmentioning
confidence: 99%